2003
DOI: 10.1093/ps/82.8.1343
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid, alpha-tocopherol, and oregano supplements reduce stress-induced deterioration of chicken meat quality

Abstract: In order to ameliorate a negative effect of stress on meat quality characteristics, chickens were fed a diet supplemented with a combination of ascorbic acid (1,000 ppm) and alpha-tocopherol (200 ppm) or oregano (3%), which has a high content of antioxidants. Chickens were slaughtered by cervical dislocation in the stable (no stress) or after transport and electrical stunning at the slaughter plant (stress). Activities of antioxidative enzymes (catalase, superoxide dismutase, and glutathion peroxidase) in pect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
91
3
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(118 citation statements)
references
References 39 publications
11
91
3
9
Order By: Relevance
“…Lipid oxidation results in the production of free radicals, which may lead to the oxidation of meat pigments and generation of rancid odours and flavours (Faustman & Cassens, 1989;. Young et al (2003) reported that MDA production was decreased in the pectoralis major of ascorbic acid-α-tocopherol-supplemented chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid oxidation results in the production of free radicals, which may lead to the oxidation of meat pigments and generation of rancid odours and flavours (Faustman & Cassens, 1989;. Young et al (2003) reported that MDA production was decreased in the pectoralis major of ascorbic acid-α-tocopherol-supplemented chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the importance of reducing transport stress and improving meat quality is becoming widely recognized. Dietary supplementation with some additives, such as oregano, ascorbic acid or chromium, has been proposed as effective ways to reduce stress responses or improve meat quality in transported broilers (Young et al, 2003;Perai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The idea was confirmed by Young et al who showed that herbs and spices, along with vitamins C and E (anti-oxidant vitamins) were even more effective at preventing lipid peroxidation in the tissues of birds [26]. There was a positive correlation between the total phenol concentration of herbal plants and human low-density lipoprotein oxidation in vitro [20].…”
mentioning
confidence: 88%